(untitled) (Revista Española de Derecho Internacional, 2007)
The qualification of the «marriage of convenience» must be realized according to lex fori, looking not only into the matrimonial institution but into the elements that converts it into a convenience’s marriage. To reach that concept the sole Private Law elements are not enough since the marriage is an institution in which the intervention of the State is left to feel. In this sense, the laws that control immigration (by family regrouping) as well as those that control Spanish nationality acquisition are Public Law. Both, Private and Public laws are projected on the conditions of validity of the marriage: the first ones by establishing the conditions of validity and the second ones by stating when those conditions are in default. This work, with Spanish Constitution and human rights rules as reference of the Spanish new marriage Act, analyses the marriage of convenience characters. It is to say that the above mentioned changes do not concern the possible qualification of «sham marriage». From the perspective of the validity of the matrimonial consent, it is possible to say that the «marriage of convenience» is not a question of a fraud to the law, nor a simulation or contra legem act, but an «undue use» of a juridical institution.